1999
DOI: 10.2169/internalmedicine.38.533
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Attitude Toward Consultations by a Physician without a White Coat in Japan.

Abstract: Object To knowhow Japanese patients perceive their physicians without a white coat during consultations. Subjects and MethodsThe patients whovisited a university clinic were divided into two groups: those seen by a physician in a white coat (the white-coat group) and those seen by a physician in private clothes (the private-clothes group). Questionnaires were distributed to the patients, which asked the tension and satisfaction of consultations as well as their preference for physician's attire. The answers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
47
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 4 publications
7
47
2
1
Order By: Relevance
“…Regarding the age distribution, most of our patients are within 45 years which is similar to study performed by Najafi et al 13 and McKinsty and Wang. 4 Likewise the distribution of sex and educational status is similar to study performed by Najafi et al 13 Regarding the wearing of white coat by doctor, 82.5% of our patients answered that the doctors should wear white coat which was similar to study performed by Najafi et al 13 and Ikusaka et al 14 Whereas it was differ from the study performed by Douse et al 11 which showed only 56% of patients favoured doctors wearing white coats. Our study also differ from other different study performed at different places.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the age distribution, most of our patients are within 45 years which is similar to study performed by Najafi et al 13 and McKinsty and Wang. 4 Likewise the distribution of sex and educational status is similar to study performed by Najafi et al 13 Regarding the wearing of white coat by doctor, 82.5% of our patients answered that the doctors should wear white coat which was similar to study performed by Najafi et al 13 and Ikusaka et al 14 Whereas it was differ from the study performed by Douse et al 11 which showed only 56% of patients favoured doctors wearing white coats. Our study also differ from other different study performed at different places.…”
Section: Discussionsupporting
confidence: 86%
“…5 A recent study found that 56% of patients preferred doctors to wear white coats, 6 a preference supported by other studies. 1,[7][8][9][10][11] Most found that the white coat improved many aspects of doctor-patient interaction and that the doctor was seen to be more professional, scientific, hygienic and easily identifiable. 7,8 But do patients care or even notice?…”
Section: Introductionmentioning
confidence: 99%
“…The white coat (combined with formal wear or scrubs), was the preferred attire in all circumstances. Many previous studies across specialties and across the world have shown a preference among patients for doctors who wear white coats [1,[3][4][5][7][8][9][10] . While some patients prefer the white coat for its ability to inspire confidence and ease communication [7,11] others feel it is an important means of identification distinct from the name tag [1] .…”
Section: Discussionmentioning
confidence: 99%